Wages, labor or prices: how do firms react to shocks? - Emmanuel Dhyne; Martine Druant (European Central Bank (ECB), 2010)
Survey results in 15 European countries for almost 15,000 firms reveal that Belgian firms react more than the average European firm to adverse shocks by reducing permanent and temporary employment. On the basis of a firm-level analysis, this paper confirms that the different reaction to shocks is significant and investigates what factors explain this difference. Although the explanatory value of the variables is limited, most of the explanatory power of the model being associated with the dummy variables coding for firm size, sector and country, the variables investigated provide valuable information. The importance of wage bargaining above the firm level, the automatic system of index-linking wages to past inflation, the limited use of flexible pay, the high share of low-skilled blue-collar workers, the labor intensive production process as well as the less stringent legislation with respect to the protection against dismissal are at the basis of the stronger employment reaction of Belgian firms. On the contrary, employment is safeguarded by the presence of many small firms and a wage cushion.
Keywords: D21; E30; J31; 330; Cost-push shocks; demand shock; indexation; survey; wage bargaining institutions; wage rigidity; Beschäftigungseffekt; Lohnrigidität; Produktionskosten; Gesamtwirtschaftliche Nachfrage; Lohnbildung; Lohnindexierung; Belgien; EU-Staaten